MINAWISATA PERIKANAN AIR PAYAU DI DESA SUNGAI CUKA TANAH LAUT - Fahma, Rayhani; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The brackish water aquaculture area in Sungai Cuka Village used to be the location of a pond that produced a lot of brackish water fish such as Milkfish (Chanos chanos), Windu Shrimp (Penaeus monodon), Mullet (Mugil cephalus), Mangrove Crab (Scylla serrata), White Snapper ( Lates calcarifer), and others. Coal mining has begun to be opened upstream of the estuary so that coal waste is carried downstream and pollutes the pond water which causes the ponds to die. This has an impact on the income of the fishermen who began to decline, finally they decided to leave the pond to look for other livelihoods. So the problem raised is how to design a brackish water aquaculture educational recreation area with a regional locality approach? This writing aims to restore aquaculture activities in Sungai Cuka Tanah Laut Village as an effort to revive dead aquaculture areas and settlements supported by pond water conditions that are free from coal waste pollution. The step to achieve the goal is to design a brackish water fishery tourism area based on educational recreation tourism. The method applied is a contextual architectural approach which is expected to maintain the characteristics of the coastal area, can renew the image of the aquaculture area which is slowly disappearing, and become a recreational tourism and fisheries education area.